Recent Progress of 3d Transition Metal Single‐Atom Catalysts for Electrochemical CO2 Reduction. Issue 5 (31st December 2020) - Xu, Chaochen; Vasileff, Anthony; Zheng, Yao; Qiao, Shi‐Zhang
Abstract: Recent studies have shown that single‐atom catalysts (SACs) have significantly better catalytic activity and selectivity for the electrochemical CO2 reduction reaction (CRR) compared to their bulk metal and nanostructured counterparts. However, there are few relevant articles reviewing SACs for the CRR, despite their importance in the field. Herein, the scope of this review is the recent development of single‐atom 3d‐block transition metal catalysts (metal = Mn, Fe, Co, Ni, Cu, Zn) and their application as electrocatalysts for the CRR. The recent representative works by metal are summarized. Results show that 1) Ni and Fe SACs exhibit superior catalytic performance for CO evolution; 2) Co, Mn, Zn SACs are less reported due to their relative inertness for the CRR; 3) Cu SACs have ordinary catalytic activity for the CRR, however, C2 products are observed in a few reports. Point (3) is attractive to the prospective study of CO2 to highly reduced products. Finally, some suggestions for the future development of SACs for the CRR are briefly proposed. Abstract : This review highlights graphene‐supported 3d transition metal single‐atom catalysts (SACs) for electrochemical CO2 reduction. Faradaic efficiencies (FEs) for CO on SACs and their corresponding applied potentials are illustrated in the scatterplot. For Ni and Fe SACs, higher FEs for CO are commonly observed. For the others, a scattered distribution is observed. Noteworthily, some Cu SACs are selective towards C2 products.